Utilizing Nanocarriers in enhancing the activity of herbal medicines Targeting Androgen Receptor Signalling in Prostate Cancer - Ahmed, Firdaus (Sulaimani Journal for Pure and Applied Sciences, 2025)
Prostate cancer remains a leading malignancy among males, with androgen receptor signaling playing a critical role in tumor initiation, progression, and resistance to therapy. Conventional treatments, including androgen deprivation therapy and AR antagonists, have shown efficacy but are often associated with significant side effects and the eventual development of castration-resistant prostate cancer. In response to these challenges, herbal nanomedicine has emerged as a promising alternative, combining the therapeutic potential of bioactive herbal compounds with the precision of nanotechnology to enhance treatment efficacy. This review highlights the role of herbal and herbal nanomedicine targeting AR signaling in prostate cancer. Herbal compounds such as curcumin, quercetin, resveratrol, and berberine have demonstrated anti-androgenic, anti-inflammatory, and pro-apoptotic effects. However, their clinical application is often hindered by low bioavailability, rapid metabolism, and poor solubility. Nanotechnology-based drug delivery systems, including lipid-based nanoparticles, polymeric nanoparticles, metallic nanoparticles, liposomes, and exosomes, offer significant advantages by improving the solubility, stability, and targeted delivery of these phytochemicals to tumor sites. Nanomedicine enhances drug accumulation in prostate cancer cells, minimizes systemic toxicity, and allows controlled drug release, thereby improving therapeutic outcomes. Additionally, nano formulations facilitate combination therapies, integrating herbal compounds with standard chemotherapeutics or AR inhibitors to overcome drug resistance. In vivo studies have shown the role of herbal nanomedicine in suppressing AR activity, modulating tumor microenvironments, and inducing apoptosis in prostate cancer cells. The integration of herbal therapeutics with nanotechnology represents a novel, targeted approach that could revolutionize prostate cancer treatment by offering safer and more effective alternatives to current
Keywords: Prostate cancer; Androgen receptor Signalling; Herbal medicine; Nanomedicine; Drug delivery; Targeted therapy